Establishment of Special Guardians for Foster Children in Child Social Welfare Institutions in Indonesia - Suryati Endang Prasetyawati (Faculty of Law, Universitas Pekalongan, 2025)
This legal research seeks to ascertain the legal status of Child Social Welfare Institutions, the procedures for guardianship, and the legal obligations of these institutions regarding guardianship, in accordance with the Criminal Code, Law, and Permensos Number 30/HK/2011 pertaining to National Childcare Standards for Child Social Welfare Institutions in Indonesia. This legal research constitutes an empirical investigation on a descriptive Child Social Welfare Institution. The study methodology employs a legislative framework. The data comprises primary data derived from empirical study findings and secondary data sourced from library books pertinent to the issue or research subject. This research reveals that the process for appointing a special guardian for foster children is explicitly governed by Permensos Number 30 / Huk / 2011 about National Childcare Standards for Child Social Welfare Institutions, particularly by a court order. The transfer of custody from parents to the Orphanage occurs immediately upon the child's submission, regardless of whether it is initiated by the parents or the appropriate agencies. This is executed due to its perceived simplicity and minimal time and financial expenditure, ensuring rapid fulfillment of demands. The legal obligations of guardianship by the Child Welfare Institution include responsibility for the child's welfare, assets, and guardianship that lacks a valid legal basis